Strategic Decision Making Analysis in Responding to Post-Pandemic Market Dynamics: Case Study on FMCG Company (PT Indofood Sukses Makmur Tbk) - Nabitha Widiya Berliana; Alya Hastin Nafisah; Jesslyn Olyvviane; Rusdi Hidayat N; Indah Respati Kumalasari (Finance : International Journal of Management Finance, 2024)
This study aims to analyze the strategic decision-making of PT Indofood Sukses Makmur Tbk in responding to market dynamics post-COVID-19 pandemic. Focusing on product diversification, digital marketing, and supply chain optimization, the study adopts a descriptive approach using qualitative methods and secondary data. The findings reveal that Indofood has successfully adapted by launching health-oriented products, expanding distribution through digital platforms, and optimizing operational efficiency. However, challenges such as dependency on imported raw materials and sustainability pressures remain significant concerns. With appropriate strategies, Indofood has the potential to strengthen its position in the FMCG industry, both domestically and internationally.